Managing multimedia equipment - Jeves, Carol (DocMatrix, 2000)
This book is a simple illustrated introduction to audiovisual equipment for non-technicians looking after video and audio equipment, projectors, photocopiers, scanners and fax machines, making purchase proposals and keeping records and booking systems.